Effect of Ketamine Plus Electroconvulsive Therapy (ECT) in Treatment of Major Depresive Episode: A Pilot Study - Vichaikosol, Tanya; Ittasakul, Pichai; Lekprasert, Varinee (Journal of the Psychiatric Association of Thailand, 2017)
Objective : To assess the efficacy of ketamine plus electroconvulsive therapy (ECT) compare with ECT alone for treatment of major depressive episode in major depressive disorder and bipolar disorder Method : A double-blind randomized control trial was conducted between July 2015 to July 2016. Subjects included patients with major depressive episode who received inpatient ECT at department of psychiatry, Ramathibodi Hospital, Bangkok.Twelve patients were randomized into 2 groups, the experimental group received ketamine 0.5 mg/kg plus ECT (n =7) and control group received ECT alone(n =5). Montgomery-Asberg depression scale (MADRS) was used to assess depressive symptoms at baseline, after first ECT, after third, then after three consecutive ECTs until the end of treatment. Hemodynamic changes and adverse events were recorded. Results : MADRS score of experimental group had greater decrease than control group after third ECT evaluation (p=0.047). Remission rate after sixth ECT evaluation in experimental group was higher than control group (p=0.048). No statistical significance between control and experimental group was detected in hemodynamic changes and adverse events. Conclusion : Intravenous injection of ketamine 0.5 mg/kg plus ECT could accelerate the effect of ECT in depressive patients during the initial phase. But ketamine injection does not increase the effect of ECT at the end of treatment.